Al-Khṭāb al-Ḥubbī fī at-Turātha al-: Arabīy: al-falsafīy wa al-kalāmīy wa al-taṣwufīy wa al-a’dabīy. - Zam-Zam Afandi Abdullah (Al-Jami'ah: Journal of Islamic Studies, 2001)
ln intellectual tradition of Islam, Philosophy, Theology, Sufism,  besides Arts had been developed rapidly. Almost all human problems become their object of study. Among them is problem of love that is rarely studied.  This article tries to study problem of "love" in the discourses of the above knowledge in general. In Philosophy, the discourse of love is related closely to two problems, namely the creation of the universe and the impacts of its movements. The first problem has been dealt by such Muslim scholars as Ibnu Qayyim al-Jauziyah, while the second has been developed by the philosophers who grouped themselves in Ikhwan al-Shafa. In Sufism, the discourse of love has its own meaning. Love for Sufi is not only the problem of relationship between peoples or merely concepts as being thought by philosophers and theologians. For them, love has become medium or highest stage which connect and even unifier between them and God (Ittihad). This meaning also differentiates love in the discourse of the Arts which only limits its discussion on the relationships between human beings.